2018
DOI: 10.1021/acsbiomaterials.8b00342
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osseointegrative Properties of Ultra-Fine-Grained Titanium Implants Modified by Chemical Etching and Atomic Layer Deposition

Abstract: An integrated approach combining severe plastic deformation (SPD), chemical etching (CE), and atomic layer deposition (ALD) was used to produce titanium implants with enhanced osseo­integration. The relationship between morphology, topography, surface composition, and bioactivity of ultra-fine-grained (UFG) titanium modified by CE and ALD was studied in detail. The topography and morphology have been studied by means of atomic force microscopy, scanning electron microscopy, and the spectral ellipsometry. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Conformal titanium oxide nanocoatings, silver NPs, and structures combining coatings and NPs have been successfully prepared by ALD. According to a number of in vitro and in vivo studies, it is known that ALD titanium oxide films have a positive effect on the proliferation, differentiation and osseointegration of titanium implants [ 19 , 30 , 31 ]. According to our results, as-deposited ALD TiO 2 coatings have a less hydrophilic surface than polished titanium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformal titanium oxide nanocoatings, silver NPs, and structures combining coatings and NPs have been successfully prepared by ALD. According to a number of in vitro and in vivo studies, it is known that ALD titanium oxide films have a positive effect on the proliferation, differentiation and osseointegration of titanium implants [ 19 , 30 , 31 ]. According to our results, as-deposited ALD TiO 2 coatings have a less hydrophilic surface than polished titanium.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained UFG rods were treated by machining as described elsewhere [ 19 , 20 ]. First, the rods were cut into discs (thickness of 2–3 mm) with the Buehler IsoMet 1000 machine (Buehler, Lake Bluff, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the application to UFG CP Ti, Nazarov and co-workers [140] modified the surface of SPD-processed CP Ti with the combination of chemical etching (piranha solution) and a 20 nm thick ALD TiO2 coating showing that the oxide coating enhanced the adhesion of osteoblasts cells with respect to both the untreated and the etched Ti surfaces in in vitro tests. In a more recent work [141], the authors demonstrated in in vivo tests that the ALD treated surface presented higher bone formation and a higher level of osseointegration through removal torque tests than both the untreated and the etched Ti screws. Fully crystalline ALD anatase films (~ 100 nm) deposited on silicon substrate at 300 ºC by…”
Section: Biocompatibilitymentioning
confidence: 98%
“…Moreover, SALD can be sensitive to ambient air if performed in open air, highly volatile precursors are needed for SALD, and, The thin film deposition technique of ALD has a wide range of applications [3,5,9,10]. Some of the important applications of ALD include but are not limited to the following areas: semiconductor engineering [11][12][13], lithium-ion batteries [14][15][16], microelectromechanical systems (MEMS) [17,18], capacitors [19,20], fuel cells [21][22][23], solar cells [24][25][26], transistors [27][28][29], drug delivery [30,31], medical and biomedical fields [32][33][34][35], dental materials [6,10], and orthopedical implants [36][37][38]. Due to the capability of precisely depositing conformal ultra-thin films, ALD has found a wide range of applications in the fabrication of microelectronics such as gate oxides, semiconductors, and ferroelectrics [12,39,40].…”
Section: Introductionmentioning
confidence: 99%